Relationship between morphological measurements of trunk in Erythrina americana Miller and yield of edible foliage - Oliva Hernández, Jorge; López Herrera, María Aurelia; Castillo Linares, Erika Belem (Ecosistemas y Recursos Agropecuarios, 2021)
The aim of this study was to analyze the relationship of diameter and height of Erythrina americana tree with the foliage yield at a regrowth age of 90 days. Forty-seven trees with height of 1.6 m ± 0.2 m, diameters of 0.085 ±0.021 and 0.065 ± 0.018 at a height of 0.20 m and 1.3 m from soil respectively were used. The relationship between height and diameters of the tree with the dry matter yield (DMY) tree-1 was determined with correlation process. The variation in DMY tree-1 was determined through multiple regression. Tree height and diameters at 0.20 and 1.3 m had a positive relationship with DMY tree-1 (p < 0.05 and p < 0.001, respectively). The diameter of the tree at 0.20 m explained 34% of the variation in DMY tree-1 (p < 0.001). Tree height and diameter did not have an important predictive value in DMY tree-1.